2022
DOI: 10.1155/2022/3588297
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Literature Examining Bacterial Urinary Tract Infections in Diabetes

Abstract: This systematic review addresses the central research question, “what is known from the published, peer-reviewed literature about the impact of diabetes on the risk of bacterial urinary tract infections (UTI)?” We examine the results from laboratory studies where researchers have successfully adapted mouse models of diabetes to study the pathophysiology of ascending UTI. These studies have identified molecular and cellular effectors shaping immune defenses against infection of the diabetic urinary tract. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 158 publications
1
3
0
1
Order By: Relevance
“…We found that gram-negative bacteria were more prevalent, with Escherichia coli and Klebsiella pneumoniae being the predominant isolate, in both groups. Similar to us several other investigations evaluating ASB have found a higher proportion of Gram-negative uropathogens, in both normoglycemic and hyperglycemic pregnant women [5] , [7] , [8] , [9] , [10] , [11] . However, few have found a predominance of Gram-positive bacteria including Staphylococcus, also [3] .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that gram-negative bacteria were more prevalent, with Escherichia coli and Klebsiella pneumoniae being the predominant isolate, in both groups. Similar to us several other investigations evaluating ASB have found a higher proportion of Gram-negative uropathogens, in both normoglycemic and hyperglycemic pregnant women [5] , [7] , [8] , [9] , [10] , [11] . However, few have found a predominance of Gram-positive bacteria including Staphylococcus, also [3] .…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, we found a higher prevalence of ASB in women with GDM. The majority of prior research has reported a higher prevalence of ASB in diabetics [5] but to date, sufficient robust studies have not explored ASB in pregnant women with GDM. Scant available literature has revealed conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither age group in our study had drastically different T2DM rates compared to national T2DM rates, around 11.3%, as reported by the CDC [ 15 ]. We expected higher rates of T2DM in our populations because of the well-established notion that individuals with T2DM are at an increased risk for UTIs [ 4 ]. This finding could result from our limited sample size, especially for individuals with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Although some measures such as the control of sterility in operating rooms [ 10 ] and antibiotic prophylaxis [ 11 ] are able to reduce the incidence of these infections, these strategies cannot completely eradicate the risk of infection. Furthermore, some conditions can increase the clinical severity, including obesity, poor nutritional status, and comorbidities such as rheumatoid arthritis and diabetes mellitus [ 12 , 13 ]. Moreover, an important feature about devices-related infections is that causative strains, including Gram-positive [e.g., Enterococcus faecalis , Staphylococcus aureus including methicillin-resistant strains (MRSA), Staphylococcus epidermidis , and other coagulase-negative staphylococci (CoNS)] and Gram-negative bacteria (e.g., Klebsiella pneumonia , Pseudomonas aeruginosa , Acinetobacter baumannii , Escherichia coli , and Proteus mirabilis ), are often able to produce biofilm [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%